Students’ Classroom Silence and Hopelessness: The Impact of Teachers’ Immediacy on Mainstream Education - Juma, Osman; Husiyin, Maysigul; Akhat, Asat; Habibulla, Imirhamza (Frontiers in Psychology, 2022)
The students’ silence in the classroom has lately become an area of attention of educators and scholars similarly; however, the factors influencing students’ classroom silence are not mainly scrutinized. This construct has been regarded as a problem of the communication between the educator and the learners that not only impact completing the teaching objectives in the classroom but also is not valuable to the nurturing of learners’ achievement. In addition, teachers positively have a noteworthy function in learners’ growth and progress and its behavior such as teacher immediacy remains a significant issue towards stimulating effective educational methods. Whilst teacher immediacy in a classroom setting is important, there is growing awareness about its important effect on learners’ silence and hopelessness. This review tries to provide some considerations about the relationship between teacher immediacy, both verbal and non-verbal, and students’ active silence and hopelessness. Successively, some suggestions are offered to lighten the practice of educators, learners, and teacher instructors.